Growing from incipient to potentially large cycle networks: screening the road network of the consolidated urban area of Lisbon - Moura, Filipe; Silva, Joana Magalhães da; Picado Santos, Luis (European Journal of Transport and Infrastructure Research, 2017)
Many arguments sustaining active modes of transport are related to ameliorating urban life. Biking should be one option for our daily trips including utilitarian trips and not only trips for leisure. Accordingly, designing cycle networks that meet citizens’ requirements for daily trips is important to increase modal share. Particularly, it should take into account coherence, directness and attractiveness/comfort, not overlooking safety issues towards other road vehicles. Furthermore, it must consider also the current limitations of existing roads (lane width or gradient), in order not to hinder excessively existing road traffic while rearranging the carriageway for suitable cycle network. These objectives become more challenging when aiming to enlarge an incipient cycle network and make it grow to a large and ubiquitous one, in hilly and consolidated urban areas. The present research proposes a practice-ready method to be implemented for screening the existing road network to potentially rearrange the existing carriageway and accommodate a cycling network in urban areas with such characteristics. The methodology suggests also key indicators to analyze the potential performance of the cycle network, at an early planning stage. Although applied to Lisbon, the cycle network screening method is potentially relevant for countries where major urban agglomerations stand in hilly land and still want to see their cyclists grow in the next years. We conclude that it is possible to potentially fit a large cycle network of almost 20% of Lisbon’s total road network. The possible network configurations obtained are assessed in terms of coherence, directness and attractiveness/comfort for bikers. Finally, construction costs of the cycle networks obtained were compared.